Sedimentary Dynamics of the Central South Yellow Sea Revealing the Relation Between East Asian Summer and Winter Monsoon Over the Past 6000 years - Lyu, Wenzhe; Fu, Tengfei; Hu, Zhangxi; Tang, Ying Zhong; Chen, Guangquan; Xu, Xingyong; Chen, Yanping; Chen, Shenliang (Frontiers in Earth Science, 2021)
The mud areas of East Asian marginal seas record considerable information about regional environmental evolution. However, debate continues regarding the relative importance of the major factors in regional sedimentary dynamics, i.e., the East Asian summer monsoon, East Asian winter monsoon, and oceanic circulation. In this study, we investigated the characteristics of grain size from a gravity core obtained in the South Yellow Sea to reveal changes in sedimentary dynamics since 5000 yr BP, and to elucidate the relationship between the East Asian summer monsoon and the East Asian winter monsoon. We found that the mean grain size was in the range of 6.9–7.8 Φ, the sediment was poorly sorted within a small range [1.2, 1.5], and the M values from 4.7–6.7 μm and most of the C values from 24–65 μm suggested pelagic suspension transport. Results indicated that the intensity of both the East Asian summer monsoon and the East Asian winter monsoon showed a fluctuating trend of decrease after approximately 5000 yr BP, and that the relationship between them was generally anticorrelated. Based on these results, we suggest that positive correlation between the East Asian summer monsoon and the East Asian winter monsoon usually results in the fall or establishment of ancient dynasties in the Central Plains of China and that negative correlation between them is controlled by strong solar radiation. Weakening of solar radiation leads to weakening of the ability to regulate the correlation between the East Asian summer monsoon and the East Asian winter monsoon, at which time the North Atlantic Oscillation plays a modulating role.